Karakteristik Pembelajaran Jarak Jauh pada Pembelajaran Tari Betawi (Persepsi Bagi Mahasiswa Tari UNJ) - Heriyani, Desi; Devi Triana, Dinny; Suwandi, Tuteng (Jurnal Pendidikan Tari, 2021)
This study aims to collect data regarding the characteristics of distance learning in Betawi Basic dance learning, perceptions for dance students at UNJ. This research was a descriptive survey research. The sampling technique used was Simple Random Sampling, with the number of research 50 students of the 2020 Dance Education Study Program who were taken randomly. The data collection technique for research instruments used Google forms to determine the characteristics of distance learning in Betawi dance learning by measuring the students’ perceptions. Analysis of the data used to test the relationship between indicators was the Pearson correlation analysis. The results obtained for this study indicated that the characteristics of distance learning were measured through students’ perceptions. Based on this research, it can be concluded that students of the Betawi Basic dance subject in the Dance Education Study Program of the State University of Jakarta have a high perception of the characteristics of distance learning, only have a deficiency in enrichment which only has 57%.The existence of this research can help students to know and understand the characteristics better of distance learning before starting the lesson, in order to maximize their abilities and attitudes in the upcoming learning process.